Protective effects of Pithecellobium dulce seed extract on sodium fluoride-induced neurotoxicity in rats - Babbanna Yelugudari; Bhaskar Nagilla; Pratap Reddy Karnati (Journal of Applied Pharmaceutical Research, 2026)
Background: According to epidemiological research, fluoride is a developmental neurotoxicant that lowers children's IQ scores. Fluoride induces oxidative stress in the brain, which can cause histological damage. This study aims to test the antioxidant potential of the methanolic extract of Pithecellobium dulce seeds. Methodology: By using different in vivo assays such as inhibition of DPPH activity in plasma, Glutathione Peroxidase (GSH-Px) activity in the brain, and histology of the cerebral cortex on days 1, 10, 20, and 30 with both Hematoxylin &Eosin and Cresyl violet stains. Results and Discussion: The methanolic extract of P dulce seeds significantly enhances GPx activity in a dose-dependent manner, effectively countering oxidative stress and providing neuroprotective benefits against fluoride-induced neurodegeneration. Results also showed the strong antioxidative potential of PDME, particularly in mitigating NaF-induced oxidative stress, as evidenced by sustained high DPPH radical-scavenging activity in the treated groups over time. An H&E histology study highlights the neuroprotective effects of PDME against NaF-induced neurodegeneration, demonstrating that PDME treatment significantly reduces neuronal loss and preserves cellular integrity, particularly at higher doses. Cresyl violet stain demonstrates that PDME has a neuroprotective effect against NaF-induced neurotoxicity, as evidenced by the preservation of neuronal morphology and Nissl substance. The study demonstrates that the methanolic extract of Pithecellobium dulce seeds exhibits significant antioxidant activity, effectively counteracting fluoride-induced neurotoxicity and preserving neuronal integrity by enhancing glutathione peroxidase activity and improving histological outcomes. Conclusion: These findings suggest that P. dulce may serve as a potential neuroprotective agent against fluoride-related cognitive impairments.